Correlation between Bone Turnover Markers and Bisphosphonates Treatment in Postmenopausal Osteoporosis - Khan, Adnan; Hanif, Muhammad; Akhtar Ahmed, Akhtar Ahmed; Habib, Salman; Kamal, Shahid (International Journal of Pathology, 2018)
Objective: To find out the significance of bone turnover markers in management of osteoporotic patients andcorrelation to bisphosphonate treatments.Design: Comparative, prospective, managerialSetting: Karachi Institute of Radiotherapy and Nuclear Medicine (KIRAN), Karachi.Material and Methods: A total of 180 post-menopausal women were selected for the study by taking the verbalconsent. Test patients were divided into five groups of 30 patients each on the basis of medicines they receive.Bisphosphonates (alendronates and risedronates) were prescribed to the patients under different brand names asfosamax, drate, osto, dronate and actonel. Serum osteocalcin, alkaline phosphatase and c-telopeptidase wereselected as bone turnover markers and were assessed quarterly to find out the correlation between these markersand different treatment groups.Results: The selected bone turnover markers i.e, alkaline phosphatase, osteocalcin & c-telopeptide were found todrop continuously at different rates in all patients undergoing treatment while in controls these markersremained same with no significant changes throughout the year. The maximum fraction drop was found intelopeptide levels and minimum drop in alkaline phosphatase, while osteocalcin levels were lying in between.Conclusion: Results showed that ALP is a good marker for indicating drug compliance but is weak for responseprediction, at 3 and 6 months. Osteocalcin has slightly less sensitivity but better specificity therefore consideredas moderate value marker. However, c-telopeptide showed high sensitivity and specificity as early as 3 monthsand thus can be considered as an excellent and high value marker for predicting treatment response.